Comparison of osteological methods applied to the fish Psectrogaster amazônica Eigenmann & Eigenmann, 1889 (Characiformes: Characidae) - Cavalcante Santiago , Leticia (2025)
The fish Psectrogaster amazonica Eigenmann & Eigenmann, 1889 (Characiformes: Characidae), known locally as “branquinha” in the Tocantins region of Maranhão, is a freshwater species found in the Tocantins River, Brazil. The main objective of this study was to conduct an osteological analysis using anatomical techniques to better understand biodiversity and enable more detailed investigations. Five osteological methods were tested to assess preservation, practicality, and efficiency: immersion in glycerin, immersion in hydrogen peroxide, dissection, dissection with hot water, and burial. The results indicated that immersion in hydrogen peroxide and dissection with hot water were the most effective methods, facilitating the removal of soft tissues and preserving bone structures. Glycerin preserved the structures well but made dissection more difficult. Hydrogen peroxide, after three days, softened the tissues, allowing for easy removal. Burial, which lasted 60 days, was not effective for bone preservation, although it completely degraded soft tissues. Manual dissection, performed over three hours, proved effective in carefully preserving the structures. Dissection with hot water was the most efficient method, as it quickly softened tissues, facilitating the process. Based on these results, the osteological studies of the branquinha proved relevant for understanding the biodiversity of Amazonian fish. All tested methods and products contributed to the observation of the specimen’s bone structures, with hydrogen peroxide being suitable for bone maceration and dissection with hot water providing clear evidence of anatomical features.